Analisis Analisis Hasil Belajar Matematika Siswa KELAS VII SMP Negeri 1 Banyudono Tahun Ajaran 2024/2025 - Aidah, Aulia Putri; Astuti, Wiwin (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the mathematics learning outcomes of grade VII students of SMP Negeri 1 Banyudono for the 2024/2025 school year. The research data was obtained from the summative assessment value by applying a quantitative descriptive method. The simple random sampling technique was used to select samples so that grades VII A – C totaling 96 students were obtained. The results of the study indicate that the mathematics learning outcomes of students are relatively low. This can be seen in the results of the analysis which indicated that 9 students or 9% were in the high category, 23 students or 24% were in the medium category, and 64 students or 67% were in the low category. It is clear that there is a substantial difference between high and low category students and there are still 80 students whose grades are below the KKM. Thus, it is hoped that this research can be the basis for improvement efforts in optimizing learning evaluation, so that the approach applied can be more in line with the needs of students and improve their learning outcomes